Effect of Sr2+ ions on crystallization process of CaCO3 in presence of EDTA, NTA and Mixture of EDTA and NTA - K Sanjiv Raj, M Nirmaladevi, V K Subramanian (International Journal of Advanced Science and Technology, 2020)
Calcium carbonate scale samples were synthesized with different amounts of strontium ion in the presence of ethylenediamminetetraacetic acid (EDTA), Nitrilotriacetic acid (NTA) and mixture of EDTA and NTA (blended) at 100 °C and compare with blank samples (prepared without EDTA and NTA). The samples were characterized using XRD, FTIR and FESEM techniques. The details revealed that in absence of any chelating agent, NTA and EDTA-NTA blended system facilitated stabilization of calcite and aragonite. Presence of EDTA stabilizes calcite more efficiently at all the amounts of strontium ions. It was also observed that increasing the amount of strontium ions influenced the morphology and the particles size whereas no significant effect was observed on the polymorphic composition.